Chronic obstructive pulmonary disease in never-smoking dairy farmers - Saso Stoleski; Jordan Minov; Jovanka Karadzinska-bislimovska; Dragan Mijakoski (My University, 2015)
Work-related chronic obstructive pulmonary disease (COPD) represents a considerable part of the disease burden globally.
Keywords: Airflow limitation; bronchodilator testing; farming; job exposure; questionnaire; spirometry